Stimulating Early Reading Skills in Early Childhood Through Digital Book Media - Sari, Dwi Lyna; Ismawati, Dwi; Afrodita, Meli; Lazfihma, Lazfihma (Indonesian Research Journal on Education, 2024)
This study aims to evaluate the effectiveness of digital books in enhancing the early reading skills of children aged 5-6 years at PAUD IT Auladuna I, specifically within Group B, in 2024. The research employed a quantitative experimental method, utilizing a stratified random sampling technique to select a sample of 28 children from the entire population. Data were collected through documentation and observation, employing reading ability tests that assessed indicators such as reading independence, simple word recognition, comprehension, and pronunciation of vowels and consonants. The data analysis included normality and homogeneity tests, followed by a t-test to evaluate the hypothesis. The results indicated a significant positive effect of digital book usage on reading skill improvement, evidenced by a calculated tcount > ttable, namely 2,760 >1,691. These findings demonstrate that integrating digital books in educational settings can stimulate early reading development among young learners. Educators are encouraged to adopt digital media in their teaching practices to foster children's literacy. Furthermore, this research provides a foundation for future studies to investigate additional effective learning media that support literacy development.